2019
DOI: 10.1111/ejn.14593
|View full text |Cite
|
Sign up to set email alerts
|

Light aerobic exercise modulates executive function and cortical excitability

Abstract: Single bouts of aerobic exercise can modulate cortical excitability and executive cognitive function, but less is known about the effect of light-intensity exercise, an intensity of exercise more achievable for certain clinical populations. Fourteen healthy adults (aged 22 to 30) completed the following study procedures twice (≥7 days apart) before and after 30 min of either light aerobic exercise (cycling) or seated rest: neurocognitive battery (multitasking performance, inhibitory control and spatial working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 53 publications
4
42
1
Order By: Relevance
“…In the meantime, although the effect size of general cognitive function was negative, Debreceni-Nagy found that of working memory and processing speed was positive. Recent study also indicate low-intensity training is beneficial for executive function and cortical excitability (Morris et al, 2020), so it is still recommended for the deconditioned survivors. However, in our analysis, vigorous-intensity exercise did not return cognitive benefits, either.…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime, although the effect size of general cognitive function was negative, Debreceni-Nagy found that of working memory and processing speed was positive. Recent study also indicate low-intensity training is beneficial for executive function and cortical excitability (Morris et al, 2020), so it is still recommended for the deconditioned survivors. However, in our analysis, vigorous-intensity exercise did not return cognitive benefits, either.…”
Section: Discussionmentioning
confidence: 99%
“…Alderman et al (2014) reported no changes in executive function during light intensity walking compared to sitting. Some previous reports have shown that cortical excitability during exercise and multitasking may preserve executive cognitive function (Morris et al, 2019), other researchers have reported cognitive decrement during the performance of concurrent exercise and mental tasks (Smith et al, 2016;Wohlwend et al, 2017). Differences in past findings may be due to exercise intensity when multitasking.…”
Section: Discussionmentioning
confidence: 93%
“…Inconsistent changes in CS excitability of a remote hand muscle (increase [20]-or stability [21][22][23][24] have been reported following locomotor exercise. Despite few data, it seems that the mode of exercisecycling vs runningmight affect CS excitability, which increased following running exercise only [20].…”
Section: Non-exercised Musclesmentioning
confidence: 99%
“…Despite few data, it seems that the mode of exercisecycling vs runningmight affect CS excitability, which increased following running exercise only [20]. Regardless of global CS excitability changes, studies using cycling consistently reported reduced cortical inhibition [21,22,25], and increased cortical facilitation [21,24]. Such modifications in the balance between cortical facilitation and inhibition for a remote muscle make the case that locomotor exercise is a promising strategy to modulate neuroplasticity for motor learning purposes.…”
Section: Non-exercised Musclesmentioning
confidence: 99%